The characteristics of human papillomavirus DNA in head and neck cancers and papillomas. Issue 1 (27th December 2004) - Major, T; Szarka, K; Sziklai, I; Gergely, L; Czeglédy, J
Abstract : Aim: To determine the prevalence, type, physical state, and viral load of human papillomavirus (HPV) DNA in cases of head and neck cancer and recurrent respiratory papillomatosis (RRP). Methods: The prevalence and type of HPV DNA was determined in 27 fresh frozen tissue specimens from patients with head and neck cancers and 16 specimens from 10 patients with RRP by MY09/MY11 and GP5+/GP6+ nested polymerase chain reaction (PCR) and subsequent restriction enzyme cleavage. The physical state of HPV DNA was analysed by E1, E2, and E1E2 specific PCRs and Southern blot hybridisation (SBH). Results: HPV DNA was detected in 13 of 27 cancers and 10 of 10 papillomas. Both low risk HPV-6 and HPV-11 and high risk HPV-16 were present in cancers in low copy numbers, whereas papillomas exclusively harboured low risk HPV-6 and HPV-11. E1E2 PCRs failed to determine the physical state of HPV in cancers except one case where HPV-6 DNA was integrated. In contrast to cancers, all papillomas showed the episomal state of HPV DNA and a relatively higher viral load. Conclusions: Based on the prevalence, type, physical state, and copy number of HPV DNA, cancers and papillomas tend to show a different HPV DNA profile. The 100% positivity rate of low risk HPV types confirms the role of HPV-6 and HPV-11 in the aetiology of RRP.